BISNIS ETIS DALAM PERSPEKTIF MORALITAS PANCASILA: SEBUAH TINJUAN KRITIS - Ngorang Philipus (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2021)
It is moral duty to manage business ethically for human solidarity and general welfare. Recognized that ethical business should be based on fairness, responsiblity, honesty, wisdom, loyality, moral integrity and no harm to the others principles. These ethical principles were found in state ideology, culture, and religioeus teachings. Indonesian state ideology is pancasila. Pancasila means five principles, that are belive on one God, fair and civilized humanity, Indonesian unity, democracy and social justice. These principles provide guidance for Indonesian people in everyday lifes as citizenship and business activities. Based on library research I found that these five principles and UUD 1945 constitution articles could support in bulding ethical activity and ethical structur in business everyday activities. It is fairness if workers salary is based on social justice values and govermental rules. Sosial justice values and govermental rules should be produced from the democracy values in salary negotiating process between business corporate and workers. These salary negotiating process should based on the unity spirit prinsiple. Pay attention to the humanity inherently comes from the unity spririt principle. And becuase we are God’s creature, pay attention to the humanity is must. In the same level, contitution article in UUD 1945 and rule law regulate rights and duties of the workers. For example, article 27 point 2 explain that every citizen should have working and way of living properly. Labour law nomor 11 tahun 2020 could be called ethical structure if this law contains of justice, democratic, unity, humanity and divinity value Key words: ethical business, pancasila morality, ethical attitude and ethical structure